Shiga toxin-producing Escherichia coli (STEC) O22:H8 isolated from cattle reduces E. coli O157:H7 adherence in vitro and in vivo - Martorelli, L (2017)
Fil: Martorelli, L. Instituto de Patobiología, CICVyA, Instituto Nacional de Tecnología Agropecuaria; Argentina.